Прибуткова нерухомість Старого Олександрівська: історико-архітектурний аспект. (Zaporizhzhia Historical Review, 2021)
In the article there was done an attempt to research the most intresting pages of the profit-making Oleksandrivsk’s townbuilding in the beginning of the XX-th century on the basis of historically-architectural approach. There is a list of examples of famous pre-rovolution buildings of the town, which are still the decoration of the Old Zaporizhzhya.